Group Guidance Services with Self-Management Interventions to Reduce Academic Procrastination Among Students - Agustina, Yuni; Mudjiran, Mudjiran (Journal of Educational, Health and Community Psychology, 2024)
Procrastination on assignments can disrupt a student’s learning process, resulting in suboptimal learning outcomes and hindering academic achievement. Without proper intervention, academic procrastination may become a significant challenge for students. Therefore, proactive measures are essential to mitigate this tendency, with one approach being group guidance utilizing self-management techniques. This study aims to assess the effectiveness of group guidance services incorporating self-management techniques to reduce academic procrastination among students. A randomized pre-post control group design was implemented, with 10 students in the experimental group and 10 in the control group, selected through random sampling. Data were collected using a Likert-scale questionnaire and analyzed via the Mann-Whitney U test, using SPSS version 20.00. The results indicate that self-management techniques are effective in reducing academic procrastination among students.